CO2-responsive anionic wormlike micelles based on natural erucic acid. Issue 2 (1st June 2014) - Yin, Hongyao; Feng, Yujun; Zhang, Yongmin
Abstract : Research interests highlighted in recent years a remarkable growing focus on stimuli-responsive surfactant wormlike micelles, particularly those using carbon dioxide as the trigger. In this article, we report a novel carbon dioxide–responsive wormlike micellar system based on natural erucic fatty acid and examined its solution properties through rheology, Fourier transform infrared spectroscopy and cryo–tranmission electron microscopy. When carbon dioxide is introduced into the erucic acid solution, high-viscelastic wormlike micelles shift to low-viscosity solutions in short-time scale, accompanied by decrease in pH from 11·34 to 8·90, which is accounted for the effect of pH on the existence form of erucic acid in aqueous solutions. Bubbling nitrogen under heating cannot make a converse process since the viscoelastic worms can only be obtained at a high pH. Compared with other carbon dioxide–responsive wormlike micelles, the current one is more readily obtained and more environment-friendly because it can be formed by simply changing pH value of the natural erucic acid solutions without needing complex organic synthesis or addition of hydrotropes.